Strategi Pemasaran Jasa Dalam Meningkatkan Daya Minat Terhadap Kun Anta Presschool - Sardini Sardini; Zakiyah Zahara; Syamsul Bachri; Risnawati Risnawati (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to explore the service marketing strategies implemented by Kun Anta Preschool, Kasturi Branch, Palu City in increasing parents' interest in this school. Kun Anta Preschool is an Islamic-based Early Childhood Education (PAUD) institution with the Montessori learning method. The research method used is descriptive with a qualitative approach. Data was collected through in-depth interviews with parents and teaching staff at Kun Anta Preschool Kasturi Branch. Direct observations were also carried out to understand practices in schools. The population of this study involved parents and teaching staff at Kun Anta Preschool, Kasturi Branch, Palu City. The research results showed that Kun Anta Preschool used several effective marketing strategies. They utilize social media such as Instagram and Facebook to create interesting content that increases the school's visibility in the community. One of the unique things about Kun Anta is the application of the Montessori learning method which is only applied by this school, which is a special attraction for parents. The obstacles faced by Kun Anta Preschool include the large school fees, but they are proportional to the facilities provided. However, the school's good reputation and the quality of early childhood education are strong factors that make parents interested in enrolling their children. This marketing strategy succeeded in increasing parents' interest in Kun Anta Preschool. In conclusion, the marketing strategy implemented by Kun Anta Preschool, Kasturi Branch, Palu City, especially through social media and unique learning methods, played an important role in increasing parents' interest. Positive factors such as the school's reputation and the quality of early childhood education also determine parents' decisions to enroll their children at Kun Anta Preschool. This research provides an in-depth understanding of how marketing strategies can influence parents' perceptions of a PAUD institution.